2017
DOI: 10.3390/ijms18040891
|View full text |Cite
|
Sign up to set email alerts
|

Commitment of Scaffold Proteins in the Onco-Biology of Human Colorectal Cancer and Liver Metastases after Oxaliplatin-Based Chemotherapy

Abstract: Scaffold proteins play pivotal roles in the regulation of signaling pathways, integrating external and internal stimuli to various cellular outputs. We report the pattern of cellular and subcellular expression of scaffoldins angiomotin-like 2 (AmotL2), FK506 binding protein 5 (FKBP51) and IQ motif containing GTPase-activating protein 1 (IQGAP1) in colorectal cancer (CRC) and metastases in liver resected after oxaliplatin-based chemotherapy (CT). Positive immunostaining for the three scaffoldins was found in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Important biological mechanisms may remodel the abundance and activity of modulatory protein hubs: Superenhancers alter both the abundance and the functions and structures at the level of protein production, and scaffold proteins act at the level of protein localization addressing their activity (45)(46)(47). Cytokines, such as interleukin-6 or TGFβ, can switch their function during tumor progression from a growth inhibitor to a growth stimulator (45,48).…”
Section: Communication Unifies All Systems Levelsmentioning
confidence: 99%
“…Important biological mechanisms may remodel the abundance and activity of modulatory protein hubs: Superenhancers alter both the abundance and the functions and structures at the level of protein production, and scaffold proteins act at the level of protein localization addressing their activity (45)(46)(47). Cytokines, such as interleukin-6 or TGFβ, can switch their function during tumor progression from a growth inhibitor to a growth stimulator (45,48).…”
Section: Communication Unifies All Systems Levelsmentioning
confidence: 99%
“…Likewise, high tumor PGE2 expression represents a key mediator of immune resistance, mainly due to the secretion of suppressive chemokines and the recruitment of MDSCs, which results in immunogenic loss. [120,121]. Regulatory T cells (Tregs) are a heterogeneous subpopulation of T lymphocytes, which play a crucial role in tolerance maintaining [122].…”
Section: Regulation Of the Antitumor T-cell Immunitymentioning
confidence: 99%
“…Accumulating data have demonstrated that FKBP51 serves important functions in tumor cell growth, apoptosis, and sensitivity to radiotherapy and chemotherapy ( 30 , 31 ). Studies have demonstrated that FKBP51 may serve a positive function in tumor progression by activating the NF-κB ( 32 34 ) pathway, or a negative function by promoting the Akt pathway through the dephosphorylation of Akt Ser473 to inhibit cell proliferation ( 9 , 35 ).…”
Section: Discussionmentioning
confidence: 99%